Enterprise penetration testing and continuous monitoring (The art of hacking series) : LiveLessons (LiveLessons (Indianapolis, Ind.), 2019)
"Enterprise Penetration Testing and Continuous Monitoring LiveLessons, part of The Art of Hacking video series, provides step-by-step, real-life complex scenarios of performing security assessments (penetration testing) of enterprise networks using internal/external reconnaissance, social engineering, and network and vulnerability scanning. You also learn how to perform web app testing, internal network testing, privilege escalation, password cracking, and data exfiltration to probe for and mitigate enterprise vulnerabilities. The course concludes with a look at reporting and evaluation methods to ensure that your enterprise environment stays secure from ever-evolving threats and security vulnerabilities."--Resource description page